The Extent of ERP Customization towards User Satisfaction in Daily Operation for Manufacturing Companies - Kanchymalay, kasturi; Amiruddin, Syuria; Salam, Sazilah; Hashim, Ummi Rabaah (Academic publisher, 2013)
Study to explore the effect of customization towards user satisfaction in the daily operation of ERP system .Study carried out in four manufacturing companies. Indepth interviews and surveys used to measure the user satisfaction in the manufacturing companies . The results reveals that exceeding certain level of customization complexity index would reduce the user satisfaction level towards the ERP system operation.